Analysis of Criminal Sanctions for Criminal Acts of Assault in Indonesia - Samsidar, Samsidar (PT. Anagata Sembagi Education, 2024)
The crime of assault is a violation of the law that often occurs in Indonesian society and has serious implications for public security and order. Assault is clearly regulated in the Criminal Code (KUHP), especially in Articles 351 to 358, which cover various forms and levels of severity of assault. This article aims to analyze the application of criminal sanctions against perpetrators of assault in Indonesia, both in the form of imprisonment and fines. Using a normative legal approach, this study examines aspects of positive law, legal doctrine, and related court decisions. It was found that although the regulations have been quite adequate, the application of sanctions still faces challenges such as inconsistency in judges' decisions, non-legal considerations, and the less than optimal role of law enforcement officers. This article also discusses the need for reformulation of the criminal sanction approach and alternative conflict resolution, such as restorative justice, to create more substantial justice. This study is expected to contribute to the development of a more humanistic and just national criminal law.